2014
DOI: 10.1101/gr.175034.114
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased analysis of potential targets of breast cancer susceptibility loci by Capture Hi-C

Abstract: Genome-wide association studies have identified more than 70 common variants that are associated with breast cancer risk. Most of these variants map to non-protein-coding regions and several map to gene deserts, regions of several hundred kilobases lacking protein-coding genes. We hypothesized that gene deserts harbor long-range regulatory elements that can physically interact with target genes to influence their expression. To test this, we developed Capture Hi-C (CHi-C), which, by incorporating a sequence ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
241
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 243 publications
(257 citation statements)
references
References 76 publications
11
241
0
1
Order By: Relevance
“…Several genome wide association studies (GWAS) have identified the 2q35 region as associated with breast cancer risk (2)(3)(4)(5). Recent work has revealed the complexity of chromatin interactions in the 2q35 region (6) and its involvement in transcriptional regulation of neighbouring gene, IGFBP5 (MIM: 146734). The 2q35 risk locus falls within a 400Kb gene desert bounded by genes TNP1 (MIM: 190231) and DIRC3 (MIM: 608262), nearby two members of the insulin growth factor binding protein family, IGFBP5 and IGFBP2 (MIM: 146731).…”
Section: Introductionmentioning
confidence: 99%
“…Several genome wide association studies (GWAS) have identified the 2q35 region as associated with breast cancer risk (2)(3)(4)(5). Recent work has revealed the complexity of chromatin interactions in the 2q35 region (6) and its involvement in transcriptional regulation of neighbouring gene, IGFBP5 (MIM: 146734). The 2q35 risk locus falls within a 400Kb gene desert bounded by genes TNP1 (MIM: 190231) and DIRC3 (MIM: 608262), nearby two members of the insulin growth factor binding protein family, IGFBP5 and IGFBP2 (MIM: 146731).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, stronger fixation conditions (i.e., higher formaldehyde concentration or longer fixation time) may increase the risk of higher background noise in single-cell Hi-C data. For dissociation to single cells and cell permeabilization, additional steps such as trypsin treatment or Dounce homogenizing may be necessary for some cell types 17 .…”
Section: Applications Advantages and Limitations Of Single-cell Hi-cmentioning
confidence: 99%
“…A number of such modifications have been published (Fig. 3b), called Capture C, Capture Hi-C (CHi-C), HiCap, and targeted chromatin capture (T2C) (Dryden et al 2014;Hughes et al 2014;Jager et al 2015;Kolovos et al 2014;Mifsud et al 2015;Sahlen et al 2015;Schoenfelder et al 2015). Most of these assays are based on hybridization of sequencing adaptor-ligated 3C (Capture C) and Hi-C samples (CHi-C and HiCap) respectively, followed by pull-down using biotinylated RNA molecules (120 nucleotides).…”
Section: Technical Limitations and Further Improvements In Hi-c Technmentioning
confidence: 99%